A triazine-based metal-organic framework with solvatochromic behaviour and selectively sensitive photoluminescent detection of nitrobenzene and Cu2+ ions. (April 2019) - Yousaf, Afifa; Xu, Na; Arif, Ali Muhammad; Zhou, Jie; Sun, Chun-Yi; Wang, Xin-Long; Su, Zhong-Min
Abstract: A novel porous triazine-based metal-organic framework, ([Cd (Ligand)]∙2DMF) (1) with strong luminescence, has been constructed via multi-carboxyl ligand 5, 5′, 5''-((1, 3, 5-triazine-2, 4, 6-triyl)tris(azanediyl))tris(3-methylbenzoic acid) under solvothermal conditions. Structural analysis revealed that MOF1 has a three-dimensional (3D) framework which is crystallized in the monoclinic system bearingC2/c space group. The high chemical and thermal stability of synthesized MOF1 has been predicted by powder X-ray diffraction and thermogravimetric analysis techniques. Higher selectivity and sensitivity of MOF1 towards Cu 2+ ions is remarkable with an adsorption capacity of 90.5 mg/g compared with Mg 2+, Mn 2+, Ni 2+, Co 2+, Zn 2+, Fe 2+ and Cr 3+ ions. Results reveal that strong emission of MOF1 can be quenched effectively by a trace amount of copper (3 ppm) and nitrobenzene (0.6 ppm), even in the vapor phase. The extraordinary solvatochromic phenomenon of MOF1 is observed by incorporating acetonitrile guest molecules due to host-guest interactions provided by the carboxyl groups of ligand and imino triazine backbone. Thus, owing to the highly selective and sensitive quenching effect in fluorescence and solvatochromic behavior, MOF1 can be used as a potential sensor for Cu 2+, NB, and acetonitrile. Graphical abstract: A novel triazine-based photoluminescent MOF was designed and synthesized, which shows solvatochromism to MeCN and highly selective sensor toward nitrobenzene and Cu 2+ ions with high sensitivity. Highlights: A novel triazine-based metal-organic framework MOF1 was designed and synthesized. The adsorptive and photoluminescence properties of MOF1 are investigated, MOF1 display high chemical and thermal stability upto 360 °C. MOF1 exhibits the tendency to selectively adsorb Cu 2+ ion with adsorption capacity of 90.5 mg/g. MOF1 is highly sensitive towards Cu 2+ ions and nitrobenzene with detection limit of 3 ppm and 0.6 ppm respectively via photoluminescence quenching, MOF1 shows good sensing ability for nitrobenzene even in vapor phase MOF1 shows rare solvatochromatic phenomenon which can be used for naked eye detection of acetonitrile molecules.